ANALISIS PENGUNGKAPAN BIAYA LINGKUNGAN (ENVIRONMENTAL COSTS) PADA PT. SEMEN INDONESIA PERSERO, TBK - MEILANAWATI, REFI (Jurnal Akuntansi AKUNESA, 2013)
This research was conducted at the manufacturing company in the field of cement, it is PT. Semen Indonesia (Persero), Tbk. This journal aims to determine how the PT. Semen Indonesia (Persero), Tbk disclose the environmental cost. Environmental costs of the company, disclosed in the annual reports and simply also presented in the financial statements. Environmental costs from PT. Semen Indonesia (Persero), Tbk can be classified based on 4 charges: environmental prevention costs, environmental detecton costs, environmental internal failure costs and environmental external failure costs. This research is a descriptive qualitative approach using secondary data derived from the study of literature. Discussion of the results showed PT. Semen Indonesia (Persero), Tbk has not record the overall environmental costs. However, in presenting the annual report of the company has been based on Law No. 40 of 2007 about incorporated company. Key words: Environmental Costs, Disclosure, Annual Report